Synthesis, characterization and computational evaluation of bicyclooctadienes towards molecular solar thermal energy storage. Issue 3 (5th January 2022) - Quant, Maria; Hillers-Bendtsen, Andreas Erbs; Ghasemi, Shima; Erdelyi, Mate; Wang, Zhihang; Muhammad, Lidiya M.; Kann, Nina; Mikkelsen, Kurt V.; Moth-Poulsen, Kasper
Abstract : Molecular solar-thermal energy storage (MOST) systems are based on photoswitches that reversibly convert solar energy into chemical energy. Abstract : Molecular solar-thermal energy storage (MOST) systems are based on photoswitches that reversibly convert solar energy into chemical energy. In this context, bicyclooctadienes (BODs) undergo a photoinduced transformation to the corresponding higher energy tetracyclooctanes (TCOs), but the photoswitch system has not until now been evaluated for MOST application, due to the short half-life of the TCO form and limited available synthetic methods. The BOD system degrades at higher temperature via a retro-Diels–Alder reaction, which complicates the synthesis of the compounds. We here report a cross-coupling reaction strategy that enables an efficient synthesis of a series of 4 new BOD compounds. We show that the BODs were able to switch to the corresponding tetracyclooctanes (TCOs) in a reversible way and can be cycled 645 times with only 0.01% degradation. Half-lives of the TCOs were measured, and we illustrate how the half-life could be engineered from seconds to minutes by molecular structure design. A density functional theory (DFT) based modelling framework was developed to access absorption spectra, thermal half-lives, and storage energies which were calculated to be 143–153 kJ mol −1 (0.47–0.51 MJ kg −1 ), up to 76% higher than for the corresponding norbornadiene. The combined computational and experimental findings provide a reliable way of designing future BOD/TCO systems with tailored properties.